The Impact of Institutional Ownership on Corporate Governance and Firm Value of Companies Listed on The Warsaw Stock Exchange: A Literature Review - Ewa BLASZKE (Communications of International Proceedings, 2025)
The rapid growth of institutional investor holdings on the Warsaw Stock Exchange has prompted questions about their capacity to enhance corporate governance and firm performance in an emerging-market setting. Although institutional activism in advanced economies is well documented, research on how Poland’s legal framework, ownership structure, and regulatory environment influence these activities remains comparatively limited. A systematic literature review of 42 key studies—spanning global theoretical frameworks and Poland-specific empirical research from 1990 to 2024—was undertaken to fill this gap. Institutional activism was classified into three forms—governance via takeovers, exit, and voice—and research designs, data sources, and analytical approaches were examined. The synthesis demonstrates that engagement through ‘voice’ mechanisms is overwhelmingly favored by Polish institutional investors, including private dialogue with management, active participation in shareholder meetings, proposal submissions, behind-the-scenes negotiations, and supervisory-board nominations. Institutional influence is found to peak when stakes range from 15%–35%. However, dispersed ownership structures, the risk of accusations of informal agreements with other shareholders, and reputational concerns constrain more confrontational tactics. Conditional improvements in monitoring quality, board composition, and Tobin’s Q were observed in the empirical studies, although the magnitude of these effects varies substantially by firm characteristics and investor type. These findings highlight the need for deeper, context-sensitive studies to uncover the mechanisms by which institutional activism creates value in emerging capital markets.
Keywords: institutional investors; corporate governance; firm value; shareholder activism; Warsaw Stock Exchange.